2017
DOI: 10.1073/pnas.1700148114
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical synchronization during induction and emergence from propofol-induced unconsciousness

Abstract: General anesthesia (GA) is a reversible drug-induced state of altered arousal required for more than 60,000 surgical procedures each day in the United States alone. Sedation and unconsciousness under GA are associated with stereotyped electrophysiological oscillations that are thought to reflect profound disruptions of activity in neuronal circuits that mediate awareness and cognition. Computational models make specific predictions about the role of the cortex and thalamus in these oscillations. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
130
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 67 publications
15
130
2
2
Order By: Relevance
“…The dynamic changes in the power law exponent correlated with fluctuation of broadband high-frequency activity. Our finding coincides with previous computational modelling and animal studies showing increased frontal corticothalamic alpha coherence associated with consciousness 13,39 . Our results are also consistent with the previous study showed reduced beta band activity in STN during general anaesthesia 19 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The dynamic changes in the power law exponent correlated with fluctuation of broadband high-frequency activity. Our finding coincides with previous computational modelling and animal studies showing increased frontal corticothalamic alpha coherence associated with consciousness 13,39 . Our results are also consistent with the previous study showed reduced beta band activity in STN during general anaesthesia 19 .…”
Section: Discussionsupporting
confidence: 93%
“…Numerous neuroimaging studies have also shown that several subcortical brain structures are involved in altered arousal and unconsciousness [7][8][9] , and it is suggested that the disruption of communication between the cortical and subcortical structures play a crucial role in anaesthetic-induced unconsciousness 8,10,11 . Therefore, investigating subcortical changes and neuronal network-level effects induced by anaesthetic drugs has become compelling and necessary for better understanding the neuronal mechanism of how general anaesthetics cause loss of consciousness [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Our data reveals that Ca V 3.2 isoform of T‐channels is relevant for the induction but not for the maintenance of 3β‐OH hypnotic effect. These channels are expressed in cortex and reticular thalamic nucleus (Talley et al, ), brain structures heavily involved in the induction of anaesthesia (Flores et al, ; Lewis et al, ). Furthermore, our previous finding revealed that Ca V 3.2 KO mice exhibited delayed onset of isoflurane anaesthesia (Orestes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…3 To this end, there are useful online educational resources 18,19 and informative journal articles. 20,21 As we learn more about general anesthesia, from the molecular to the systems neuroscience level, [22][23][24] we will be able to design a new generation of brain monitors with everstronger scientific foundations that will accord more accurately with different neurological states and depths of anesthesia.…”
mentioning
confidence: 99%
“…• 20,21 Au fur et à mesure que nous en saurons plus sur l'anesthésie générale, du niveau moléculaire jusqu'au niveau des neurosciences sur le système, [22][23][24] nous pourrons concevoir une nouvelle génération de moniteurs cérébraux avec disposant de bases scientifiques toujours plus solides qui refléteront plus précisément les différents états neurologiques et les profondeurs de l'anesthésie.…”
unclassified